Contextual Analysis of Stakeholder Opinion on Management and Leadership Competencies for Undergraduate Medical Education: Informing Course Design - Rajeh, Nisreen (J Med Educ Curric Dev, 2020)
BACKGROUND: The study aimed to conduct a contextual analysis of interviews intended to assist with the future design of a feasible and relevant leadership and management course for undergraduate medical students at King Abdulaziz University (KAU), Saudi Arabia. METHODS: This was a cross-sectional study conducted at King Abdulaziz University (KAU), Saudi Arabia, during 2019. An exploratory qualitative approach, utilizing systematic content analysis, was used. Data were collected using semi-structured interviews that were conducted with 10 leaders who were stakeholders at KAU, health service providers at KAU hospital, and stakeholders in the Ministry of Health. RESULTS: This study revealed critical findings that highlighted the areas in which KAU could instill better and adequate leadership and management skills in their undergraduate medical students. Multiple core categories for a leadership and management curriculum emerged with many interrelated themes. Most participants mentioned that leadership can be taught and that early exposure is beneficial for developing skills. Additionally, they stated that leaders should have a vision and the ability to articulate that vision. CONCLUSIONS: Different implementation challenges were described in relation to the availability of human resources, the current short supply of suitable teachers, and program design. Teaching methods recommended included simulations, lectures, and a project-based approach. Assessment methods that were recommended included objective structured clinical examination (OSCE), formative and summative assessments, self-assessments, and portfolios.